2010
DOI: 10.3168/jds.2009-2469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat stress and nutrition on lactating Holstein cows: II. Aspects of hepatic growth hormone responsiveness

Abstract: Heat stress (HS) is a multibillion-dollar problem for the global dairy industry, and reduced milk yield is the primary contributor to this annual economic loss. Feed intake declines precipitously during HS but accounts for only about 35% of the decreased milk synthesis, indicating that the physiological mechanisms responsible for decreased milk production during HS are only partly understood. Thus, our experimental objectives were to characterize the direct effects of HS on the somatotropic axis, a primary reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 41 publications
4
60
0
6
Order By: Relevance
“…Furthermore, the total amount of CORT and IGF-I tended to present a negative and significant correlation. In the same way, some studies have reported that heat stress caused a numerical decrease in IGF-I release during heat stress (Collier et al 2008;Rhoads et al 2010;Wheelock et al 2010). However, at low air temperatures, CORT are often lower and IGF-I are often higher (Richards et al 1995;Rensis & Scaramuzzi 2003).…”
Section: Time Sampling Datamentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the total amount of CORT and IGF-I tended to present a negative and significant correlation. In the same way, some studies have reported that heat stress caused a numerical decrease in IGF-I release during heat stress (Collier et al 2008;Rhoads et al 2010;Wheelock et al 2010). However, at low air temperatures, CORT are often lower and IGF-I are often higher (Richards et al 1995;Rensis & Scaramuzzi 2003).…”
Section: Time Sampling Datamentioning
confidence: 82%
“…In the same way, while some authors have reported that growth hormone (GH) and insulin-like growth factor I (IGF-I) are negatively influenced by heat stress (Sarko et al 1994;Rhoads et al 2010;Wheelock et al 2010), others mentioned that IGF-I levels during heat stress are similar to those obtained within thermal comfort zone (McGuire et al 1991;Hirayama et al 2004;Chaiyabutr et al 2008;Collier et al 2008). For these reasons, the interactions between heat stress and CORT and between IGF-I and environmental heat remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports showed that Holstein milk yield decreased during HS; feed intake and management factors partly account for the decreased milk yield during heat stress (Rhoads et al 2010, Smith et al 2013, Hill and Wall 2014. Several studies also suggested that transcription and translation of RNA in mammary epithelial cells are inhibited, as is cell cycling growth; membrane permeability is also changed during heat stress (Sonn et al 2002, Collier et al 2006&2008, Han et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress (HS) in hot climates is a major cause that strongly negatively affects milk yield and composition in dairy cattle, leading to immeasurable economic loss (Rhoads et al 2010, Smith et al 2013, Hill and Wall 2014. As we all know, cellular heat stress response is one component of the acute systemic response to HS (Collier et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The animal industry has suffered great economic losses due to the seasonal climate in many regions (Gao et al 2013;Rhoads et al 2010). Current studies have indicated that economic losses across several stock farming industries will be quite considerable without primary protection from heat.…”
Section: Introductionmentioning
confidence: 99%